A Model Of Organisational Resilience Based On Visionary Leadership And Knowledge Management: Model Resiliensi Organisasi Berbasis Kepemimpinan Visioner dan Knowledge Management - Nika Sintesa; Yunita Indriany (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyze the influence of visionary leadership and knowledge management on organizational resilience at Politeknik LP3I Jakarta in responding to the complex and uncertain dynamics of the vocational education environment. The study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The respondents consisted of 120 managerial personnel at Politeknik LP3I Jakarta, including top-level leaders, middle managers, and academic administrators, selected through proportionate random sampling. The research instrument used was a questionnaire. The results indicate that visionary leadership has a positive and significant effect on organizational resilience. Knowledge management also has a significant influence, although with a relatively small effect size. The coefficient of determination (R² = 0.733) suggests that 73.3% of the variation in organizational resilience at Politeknik LP3I Jakarta can be explained by these two independent variables, indicating a strong explanatory power of the model. These findings highlight the importance of future-oriented leadership and effective knowledge management in enhancing an institution’s ability to sustain, adapt, and grow continuously in the face of dynamic environmental challenges.